The ex ante incentive compatible core in exchange economies with and without indivisibilities - Françoise Forges (Center for Economic Studies and ifo Institute (CESifo), 2006)
The ex ante incentive compatible core of an exchange economy with private information is the (standard) core of a socially designed characteristic function, which expresses the fact that coalitions allocate goods by means of random incentive compatible mechanisms. We first survey some results in the case of perfectly divisible goods. Examples then show that the ex ante incentive compatible core can be empty, even if utility functions are quasi-linear. If, in addition to quasi-linearity, further assumptions are made (like independent private values), the non-emptiness of the core follows nevertheless from d?Aspremont and Gérard-Varet's construction of incentive compatible, ex post efficient mechanisms. We also introduce a private information version of Shapley and Scarf's economies with indivisible goods, and prove that the ex ante incentive compatible core is always non-empty in this framework.
Keywords: D82; C71; C78; 330; core; incentive compatible mechanism; indivisible goods; private information; Core; Spieltheorie; Asymmetrische Information; Ökonomischer Anreiz; Theorie